Analysis of Factors Influencing Online Shopping Behavior in the Covid-19 Pandemic : Study of the Indonesian Millenial Generation - Abdi, Tufail Rosyad; Ismail, Munawar; Satria, Dias (AIBPM Publisher, 2024)
The COVID-19 pandemic has led to significant shifts in consumer behavior, particularly in terms of shopping preferences and behavior, with a marked increase in online shopping. This study aims to re-examine the factors influencing online shopping behavior during the COVID-19 pandemic by integratingÂ framework the Theory of Planned Behavior (TPB), Technology Acceptance Model (TAM), and Cognitive Biases. The study focuses on Indonesian millennials as the target population. Data analysis is conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 3.0 software. The results show that cognitive bias, perceived usefulness, perceived ease of use, and subjective norms influence individuals' intentions to shop online. However, attitudes towards use and perceived behavioral control do not influence individuals' intentions to shop online. Finally, the results indicate that individuals' intentions to shop online impact actual online shopping behavior. The higher the individual's intention to shop online, the more certain they are to do so during the Covid-19 pandemic.